Perancangan Sistem Informasi Pendaftaran Peserta Ibadah Onsite Di GKI Serpong Dimasa Pandemi Berbasis Web - Sandy Yoan; Yakub Yakub (ALGOR, 2022)
Since the coronavirus pandemic, worship activities at GKI Serpong have been limited, including the limited number of congregants who can come to worship at the church. Meanwhile, to limit the number of congregations present, GKI Serpong uses a registration system using Google Form. The Google Form system for registration used is not effective and efficient, because the features provided by the Google Form are too few, so the congregational data needed by the church is small. Then it is necessary to create a system that is much better in terms of benefits in its use. By using the waterfall model research methodology (Waterfall), it is the most widely used and old software engineering paradigm. The Waterfall method proposes a systematic and sequential approach to software development that begins at the stage and progress of the system throughout the analysis, design design, code, testing, and maintenance. By using the Waterfall method in designing the registration system, the system created is much easier and more targeted. With the onsite worship registration system, GKI Serpong can easily monitor and limit congregations who will attend church to worship, and congregations can come again to worship onsite at the church by registering themselves easily through the system created. The system created can also be used by the church for many events other than public worship such as children's worship, youth and other fellowships in the church.